Cherophobia among students at the City of Science University College - Majid Farhan Maded (Journal of Madenat Alelem University College, 2025)
The current research aims to identify the presence of cherophobia among students at Madenat Al-Elelm University College and examin gender- based differences in its levels (male vs .female ) . to achieve these objectives, the researcher developed a cherophobia scale based on a theoretical framework. The scale consisted of (20) items. It was administered to a randomly selected sample of (300) male and female students from the college. The results indicated that college students either do not suffer from cherophobia or experience it at a very low level, there were statistically significant gender differences in cherophobia levels , with males exhibiting higher levels than females.